ΕΠΙΣΤΌΛΙΑ ΠΑΡΑΚΛΗΤΙΚΑ AND THE “LIBERATION” OF ATHENS (Годишен зборник на Филозофски факултет - Скопје, 2023)
The paper centres on the historical background in which Athens was “liberated” in c. 255. The first part explores the tenability of the assumption that the “petitions” mentioned by Diogenes Laertios in his biography of Arkesilaos should indeed be placed in the context of the “liberation” of Athens. The analysis of the chapter, as well as the particular phrase, points towards a rather different conclusion – that we are dealing with private petitions, and therefore the information should not be associated with the “liberation” of Athens; consequently, that there is no correlation with the question for the date of the battle of Kos. The second part focuses on the causes for Antigonos’ decision to “liberate” Athens; i.e., the conjecture that this decision stemmed from the victory at Kos. The analysis of the sources shows that even though the conjecture cannot be ruled out, it cannot be proven either. Lastly, an alternative context for the “liberation” of Athens is offered.